Successful heparin-perfusion therapy for complete thrombosis of the intra- and extrahepatic portal and mesenteric vein: a case report and literature review - Misbahuddin-Leis, Mohammed; Ademi, Burhan; Ankolvi, Muzaffer; Dubasz, Krisztina; Mishra, Manisha; Riechmann, Maren; Graeb, Christian; Radeleff, Boris (Radiology case reports, 2023)
The initial treatment of acute and subacute portal vein thrombosis, which is the most common cause of portal vein occlusion, consists of intravenous anticoagulation with heparin, but there is still a huge uncertainty among physicians regarding the role of more invasive therapies. We report a 61-year-old male patient, who presented in our emergency room with a subacute complete thrombosis of the intra- and extrahepatic portal vein, mesenteric vein, with associated venous congestion of 20-30 cm length of the small intestine with a quick and complete remission of the portal vein thrombosis under sole i.v. heparin-perfusor therapy without any complications. Molecular genetic analysis found combined genetic mutations of the gene factor 2 (c.20210G>A, heterozygotic), SERPINE1 (-675 5G>4G, heterozygotic), and the MTHFR gene. Along with this interesting case, we also present the recent status of portal vein thrombosis and portal vein occlusion in the literature.
Available online 21 December 2022
Gesehen am 20.10.2023